Pengaruh Fine Motor Play terhadap Kemampuan Motorik Halus pada Anak Autism Spectrum Disorder (ASD) - Sholihin, Risma Dhevtia Maharani; Prasetyaningsih, Roh Hastuti (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Autism disorders are often accompanied by fine motor problems, which can affect daily activities and children's development at school. Intervention through occupational therapy, namely fine motor play activities, is one alternative in improving children's fine motor skills. Objectives: To determine the effect of fine motor play activities on fine motor skills in children with Autism Spectrum Disorder (ASD). Methods: This study used a quantitative approach with the General Linear Model Repeated Measures (GLM-RM) Test method. The instrument used was The Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2). With a sample size of 11 autistic children using the purpose sampling technique. Results: The average BOT-2 score on the fine motor component of boys and in the age group of children (5-11 years) tended to be higher. The results of the hypothesis test using the Friedman test and repeated ANOVA obtained values ​​of 0.001; 0.024; and 0.000 (p <0.05), which means there is a difference between the average BOT-2 scores in each measurement. Conclusion: This study shows that there is an influence of fine motor play on fine motor skills in children with Autism Spectrum Disorder (ASD). Keywords: Fine motor play, Fine motor skills, Autism Spectrum Disorder (ASD)